CONTACT ANGLE MEASUREMENT OF DENTAL RESTORATIVE MATERIALS BY DROP PROFILE IMAGE ANALYSIS - H. D. K. Yulianto dan M. Rinastiti (Jurnal Teknosains, 2014)
The capability of initial microbial adhesion to dental restorative composites surface is influenced by the surface wettability of the materials. The common method to evaluate surface wettability of materials is contact angle measurement. The existing conventional method to measure contact angle is by means of a contact angle (CA)-Goniometer device, which is less practically applicable in clinical circumstances. Therefore, a more practical and applicable method is needed to measure contact angle in clinical circumstances. This research was performed to compare between contact angles measured by means of a CA-Goniometer device and a new practical method of drop profile image analysis. In addition, since there were two different formulas that can be used to calculate contact angle value from a drop profile image, then we also need to evaluate which formula is more reliable to be used. Tests were carried out using three composite discs (Clearfill-Kuraray Medical, Inc.) sample and deionised water for different measurement procedures. One drop of 3µl liquid was dropped onto the surface of the composite discs, and the drop profile image was captured by means of a customized home-made device connected to a digital camera. Two different formulas were used to calculate the contact angle value from the drop profile image, namely the “linier gradient equation” and the “tangential line”. The contact angle values obtained from the two different formulas were compared with the value obtained from the conventional method descriptively. Tests were carried out using three composite discs (Clearfill-Kuraray Medical, Inc.) sample and deionised water for different measurement procedures. One drop of 3µl liquid was dropped onto the surface of the composite discs, and the drop profile image was captured by means of a customized home-made device connected to a digital camera. Two different formulas were used to calculate the contact angle value from the drop profile image, namely the “linier gradient equation” and the “tangential line”. The contact angle values obtained from the two different formulas were compared with the value obtained from the conventional method descriptively. The differences in percentage between the contact angle value calculated by the “linier gradient equation” and “tangential line” formulas, and those calculated by means of the CA-Goniometer are 20,56% and 3,51%, respectively. It is obviously demonstrated that the value obtained by the “tangential line” formula has a smaller difference compared to those obtained by the “linier equation gradient” formula. Among the two different formulas, it is confirmed that the contact angle value calculated with the “tangential line” formula has closer similarity with the value obtained from the CA-Goniometer. This result confirms that the new practical method of drop profile image analysis is promising for measuring contact angle values in clinical circumstances. Related to the drop profile image analysis, the “tangential line” formula is more accurate compared to the “linier gradient equation” formula.